Erodibility and Runoff Potential of Laterite Soils Under Simulated Rainfall Conditions - Sajeena S (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 1999)
Soil erosion is one of the most serious environment degradation problems. However reliable measurement of erosion remains limited and estimates of soil productivity are even rarer. Assessing the extent and seriousness of erosion therefore remains a difficult task Nevertheless, identification and assessment of erosion problems could have an important role in influencing better land use and conservation practices. Rainfall simulators are considered as an effective tool in soil conservation research. Simulators make it possible to produce predetermined storms at any desired time and location. They make the replication of research easier and facilitate the study of storm sequences. Laterite soils are by far the most important soil group occurring in Kerala and cover the largest area. The objective of this study was to estimate the erodibility and runoff potential of laterite soils of three well defined series under simulated rainfall conditions. The rainfall simulator designed and fabricated by Kurien and George (1998) was modified for better performance. The modified simulator could produce rainfall intensities varying from 741 to 23.00 cmlh. Also uniformity of the rainfall produced could be increased to higher values of 88.10 and 91.53 per cent, thus giving a better performance. Intensity of rainfall increased as the